A real-world study of PARP inhibitors in 75 patients with platinum-sensitive recurrent ovarian cancer from China - Chen, Jinghong; Zhang, Mengpei; Li, Kemin; Duan, Yuanqiong; Lin, Xiaojuan; Zhong, Lan; Li, Qintong; Yin, Rutie (Frontiers in Oncology, 2024)
Objective The aim of this study is to assess the efficacy and safety of poly (ADP-ribose) polymerase inhibitor (PARPi) as a maintenance therapy for patients with platinum-sensitive recurrent epithelial ovarian cancer (PSROC) at the largest center of gynecologic oncology in Western China. Patients and methods The efficacy of PARPi was evaluated by progression-free survival (PFS) and overall survival (OS) in this real-world single-center retrospective cohort study conducted at West China Second University Hospital. The safety of PARPi was assessed using Common Terminology Criteria for Adverse Events Version 5.0. Results In this study, we included a total of 75 eligible patients, of which 54 (72.0%) received olaparib and 21 (28.0%) received niraparib. Among these patients, 24 (32.0%) had breast cancer susceptibility gene (BRCA) mutations, 27 (36.0%) achieved complete response after their last platinum-based therapy, and 22 (29.3%) had previously received ≥3rd-line chemotherapy. The median progression-free survival (mPFS) was 19.1 months (95% CI 8.5-29.7), and the median overall survival (mOS) had not been reached. Log-rank analysis revealed that age (<65 years old V.S. ≥65 years old) and previous lines of chemotherapy (2nd-line V.S. 3rd-line V.S. ≥4th-line) were associated with prolonged PFS (P <0.05). However, multivariate COX regression analysis did not identify any independent factors associated with prognosis (P >0.05). The most common grade≥3 adverse events in the olaparib group were anemia, thrombocytopenia, and leukopenia, while in the niraparib group, they were anemia and thrombocytopenia. Conclusion This study confirmed that olaparib and niraparib are effective and tolerate for PSROC in real-world settings. At the follow-up endpoint, no independent prognostic factor associated with prolonged PFS was identified.